Establishment of runway capacity index via traffic load movements - Tan, Keng Liang (2016)
Worldwide air traffic is forecasted to grow significantly and airports are looking at ways to accommodate this increasing demand. Besides constructing new runways, another approach is to maximise current capacity. Therefore, first finding the ideal maximum capacity of the airport is important as it can then be used to assess the potential increase in flight movements. In a previous final year project, a runway capacity index model has been established for Singapore Changi airport. This project is an extension of that and aims to apply its methodology to London Heathrow and Bangkok Suvarnabhumi airport. The method is based primarily on model simulation in AirTOp, and an index can be created from the simulation results. This index serves as a way to assess the runway usage efficiency of current operations. Comparing the results of the three airports shows that the methodology proposed is robust and adaptable to different airports.